2020
DOI: 10.1186/s43019-019-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Posterior condylar offset changes and its effect on clinical outcomes after posterior-substituting, fixed-bearing total knee arthroplasty: anterior versus posterior referencing

Abstract: Background: We sought to determine whether there was a difference in the posterior condylar offset (PCO), posterior condylar offset ratio (PCOR) and clinical outcomes following total knee arthroplasty (TKA) with anterior referencing (AR) or posterior referencing (PR) systems. We also assessed whether the PCO and PCOR changes, as well as patient factors were related to range of motion (ROM) in each referencing system. Methods: This retrospective study included 130 consecutive patients (184 knees) with osteoarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…However, most knees in this study lacked advanced osteoarthritis necessitating TKA, so caution is required when extrapolating our findings to clinical practice. Third, this study featured PS prosthesis, which requires consideration of the implant feature prior to any broad generalizations, as implant design has been shown to be strongly correlated with knee kinematics [ 26 , 35 ]. Generally, when performing KA TKA, a cruciate-retaining (CR) prosthesis is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…However, most knees in this study lacked advanced osteoarthritis necessitating TKA, so caution is required when extrapolating our findings to clinical practice. Third, this study featured PS prosthesis, which requires consideration of the implant feature prior to any broad generalizations, as implant design has been shown to be strongly correlated with knee kinematics [ 26 , 35 ]. Generally, when performing KA TKA, a cruciate-retaining (CR) prosthesis is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…As our cohort received PS TKAs, the weak correlations observed are unsurprising. It can be suggested that the inherent design features of the PS TKA prevent anterior translation of the femur during flexion delaying [8]. That study, however, examined 184 knees from 130 consecutive patients and primarily focused on differences between anterior-and posterior-referencing systems for measuring PCO.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy in the literature as to whether PCO impacts knee flexion after TKA [2,[4][5][6][7]. Some studies report correlation between the degree of offset and joint ROM, but others report discordance between the 2 measures [8]. Furthermore, randomized studies looking at the role of the posterior cruciate ligament in maximum postoperative flexion and functional outcome scores report no difference between posterior cruciate retaining (CR) and substituting implant designs [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In contrast, other authors state that the constitutional PCO's alteration had no significant clinical effect on the outcomes. [7][8][9][10][11][12][13] Different factors are the reason for these differences. 7 The comparison of pre-and postoperative PCO determined in "true lateral radiographs" presents several methodological errors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that PCO restoration correlates with improved functional outcomes after primary TKA and revision 2–6 . In contrast, other authors state that the constitutional PCO's alteration had no significant clinical effect on the outcomes 7–13 . Different factors are the reason for these differences 7 .…”
Section: Introductionmentioning
confidence: 99%